Do Immigrants Ever Oppose Immigration? - Aflatun Kaeser; Massimiliano Tani (Institute of Labor Economics (IZA), 2022)
This paper analyses immigrants' views about immigration, filling an important void in the immigration literature. In particular, it explores the role of statistical discrimination as a cause of possible opposition to immigration in absence of stringent immigration policies and large volumes of undocumented immigration. We test this hypothesis using US data from the 7th wave of the World Value Survey finding that successful immigrants in the US – i.e. those in the highest socio-economic group – have negative views about immigration especially with respect to its contribution to unemployment, crime, and the risk of a terrorist attack. This effect does not arise in the case of host countries that apply stricter controls on immigration, like Australia, Canada and New Zealand, or do not attract large volumes of undocumented immigrants. We interpret these results as evidence that undocumented or uncontrolled immigration negatively affects the standing of existing high socio-economic status immigrants by lowering it in the eyes of US natives, hence triggering an anti-immigration view as a response.
Keywords: D1; D89; D90; F22; J15; 330; immigration; beliefs; attitudes; behaviors